Rancang Bangun Smart Kontrol Lampu Penerangan Jalan Umum Berbasis SMS Gateway - Affan - Bachri (Jurnal JE-UNISLA : Electronic Control, Telecomunication, Computer Information and Power System, 2019)
Control street light is used in special areas that are difficult to reach by operator or officer in charge of light control street. This research is using the GSM SMS gateway and ATMEGA328 microcontroller. The aim of this research are to know design the lamp smart control of public street lighting based on SMS gateway and the smart control device to public street lighting which can do automatically and can read electric current and voltage. The method of this research is experimental by doing such as testing, measuring, registering and several experiences by using sensor LDR and SMS gateway, The principal of work to detect voltage, electric current with microcontroller ATMEGA328 and sensors. The components that use are microcontroller ATMEGA328, transformation 2 amps, IC regulator, lighting sensor, really, current sensor ACS712, voltage sensor ZMPT101b, LED lamp, GSM SIM 800L V.2 and SMS  gateway, battery 12 Volt. The finding result of this study is the way to turn on and turn off public street lighting by using automatically system, the border light that has been determined and know the current electric and voltages. Sending signals was received by the 800L V.2 SIM module. When the signal is not good, it is difficult to send SMS data to the handphone. So, it needs  additional interface or website-based program, the output of current is more than 2Amp in order to the equipment do maximize in operate the module device and the signal of GSM signal can search to the mobile.